Analyses of Genetic and Clinical Parameters for Screening Patients With Inherited Thrombocytopenia with Small or Normal‐Sized Platelets. Issue 12 (14th July 2015) - Ouchi‐Uchiyama, Meri; Sasahara, Yoji; Kikuchi, Atsuo; Goi, Kumiko; Nakane, Takaya; Ikeno, Mitsuru; Noguchi, Yasushi; Uike, Naokuni; Miyajima, Yuji; Matsubara, Kousaku; Koh, Katsuyoshi; Sugita, Kanji; et al.
<x xml:space="preserve">Abstract</x> Background Childhood thrombocytopenias include immune thrombocytopenic purpura (ITP) and inherited thrombocytopenia; the former is caused by autoantibodies to platelets, whereas the latter can be distinguished by platelet size and underlying genetic mutations. Due to limited methods for the definite diagnosis of ITP, genetic and clinical parameters are required for diagnosing inherited thrombocytopenias with small or normal‐sized platelets. Procedure In total, 32 Japanese patients with thrombocytopenia with small or normal‐sized platelets from 29 families were enrolled. All the patients were under 20 years of age, with family histories of early‐onset thrombocytopenia and/or poor response to conventional therapies for ITP. Genotypes and clinical parameters were retrospectively evaluated according to the disease type. Results Twelve cases of inherited thrombocytopenia were observed. We identified chromosomal deletions within the WASP gene in two patients with Wiskott–Aldrich syndrome; a missense mutation in a patient with X‐linked thrombocytopenia; and mutations in the RUNX1 gene of five patients with familial platelet disorder with propensity to acute myelogenous leukemia, and in the ANKRD26 gene of four patients with autosomal dominant thrombocytopenia‐2. All 12 carried germline mutations, three of which were de novo. Furthermore, we observed significantly elevated serum thrombopoietin (TPO) levels and dysplasia of megakaryocytes in patients carrying the RUNX1 and ANKRD26 mutations. Conclusions Genetic analyses and detection of TPO levels and dysmegakaryopoiesis were clinically useful for screening patients with inherited thrombocytopenias, irrespective of the family history. We hypothesize that the WASP, RUNX1, and ANKRD26 genes are important for normal TPO signaling and the network underlying thrombopoiesis. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.